Attentional bias to threat is modulated by stimulus content: an fNIRS study - Liu, Hejun; Zhang, Qihan; Elhai, Jon D.; Montag, Christian; Yang, Haibo (Frontiers in Human Neuroscience, 2024)
People are evolutionarily predisposed to associate threat relevant stimuli with fear or aversiveness and show an attentional bias towards threat. Attentional bias modification (ABM) has been shown to reduce threat biases, while quantitative reviews assessing the effectiveness of bias modification yielded inconsistent results. The current study examined the relationship between the training effect of attentional bias to threat and the type of threatening stimuli. Twenty-two participants performed a modified dot-probe task while undergoing functional near-infrared spectroscopy (fNIRS) imaging. Results indicated that there was a strong pattern of attentional avoidance among individuals in an animal but not human threat condition. Furthermore, findings from fNIRS confirmed that the influence from type of threatening stimulus would be modulated by cortical activation patterns, especially in the ventrolateral prefrontal cortices (vlPFC) and angular gyrus. Overall, these results suggest that stimulus-specific may play a major role in personalization of specific psychological interventions.